2023
DOI: 10.1111/ijcs.12963
|View full text |Cite
|
Sign up to set email alerts
|

Examining the context‐specific reasons and adoption of artificial intelligence‐based voice assistants: A behavioural reasoning theory approach

Abstract: AI‐based voice assistants are some of the most popular consumer products of artificial intelligence technology. This study investigates the influence of the reasoning process on overall consumer attitudes and adoption intentions towards AI‐based voice assistants. Behavioural reasoning theory was applied to hypothesize relationships between values, context‐specific reasons, attitudes, and adoption intention. Partial least squares structural equation modelling was used to test the research model and hypotheses u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 112 publications
0
13
0
Order By: Relevance
“…Interestingly, the study also reveals that brand credibility can moderate the relationship between perceived privacy risk and perceived value, suggesting that high brand credibility can mitigate privacy concerns, thereby enhancing loyalty towards the brand , Maroufkhani et al, 2022. The work of Anayat, Rasool & Pathania (2023) provides insights into how voice assistants affect consumer behavior across different environments and demographics. Their research indicates that while the importance of VA attributes remains consistent across environments, the value placed on these attributes varies (Adeoti, Olawale & Raji, 2018.…”
Section: Defining the Scope: Voice Assistants In Consumer Behavior An...mentioning
confidence: 86%
See 1 more Smart Citation
“…Interestingly, the study also reveals that brand credibility can moderate the relationship between perceived privacy risk and perceived value, suggesting that high brand credibility can mitigate privacy concerns, thereby enhancing loyalty towards the brand , Maroufkhani et al, 2022. The work of Anayat, Rasool & Pathania (2023) provides insights into how voice assistants affect consumer behavior across different environments and demographics. Their research indicates that while the importance of VA attributes remains consistent across environments, the value placed on these attributes varies (Adeoti, Olawale & Raji, 2018.…”
Section: Defining the Scope: Voice Assistants In Consumer Behavior An...mentioning
confidence: 86%
“…The scope of voice assistants in shaping consumer behavior and brand loyalty is multifaceted. The studies by Maroufkhani et al (2022), Anayat, Rasool, & Pathania (2023) collectively highlight the critical role of voice assistants in modern consumerism. They demonstrate that voice assistants are not merely tools for convenience but are pivotal in shaping consumer perceptions, preferences, and loyalty towards brands.…”
Section: Defining the Scope: Voice Assistants In Consumer Behavior An...mentioning
confidence: 99%
“…Numerous studies, i.e., refs. [ 15 , 21 , 23 , 31 , 33 , 34 ] showed that when students convey a positive BI towards ChatGPT, signifying their readiness to include it in their routines or tasks, there is a heightened probability this intention being translated into actual use. Furthermore, the more substantial the intention to use ChatGPT, the more likely students are to engage in active interaction with the platform, seek its assistance, and integrate it into their academic activities [ 13 , 29 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…When examined in the context of artificial intelligence-based technologies, Behavioral Reasoning Theory (BRT) is used to examine the effect of attitude on intention [109][110][111][112]. For example, Anayat et al (2023) [109] investigated context-specific reasons and consumer adoption of AI-based voice assistants using the Reasoning Theory approach and revealed that attitude plays an important role in the intention to use AI-based voice assistants.…”
Section: The Effect Of Attitude Towards Use On Intention To Usementioning
confidence: 99%
“…When examined in the context of artificial intelligence-based technologies, Behavioral Reasoning Theory (BRT) is used to examine the effect of attitude on intention [109][110][111][112]. For example, Anayat et al (2023) [109] investigated context-specific reasons and consumer adoption of AI-based voice assistants using the Reasoning Theory approach and revealed that attitude plays an important role in the intention to use AI-based voice assistants. Similarly, Wagner et al (2023) [110] conducted a configuration analysis to understand potential doctors' intentions to use AI in their future medical practices and revealed that a strong belief in the role of AI is required for the intention to use AI.…”
Section: The Effect Of Attitude Towards Use On Intention To Usementioning
confidence: 99%